REREADING PRIMARY SOURCE FOR DOCUMENTATION OF GEOGLYPHS IN THE LOWER CHILLON RIVER VALLEY, CENTRAL COAST OF PERU - Carranza Orbegoso, Jorge (2010)
Recent investigations show the presence of geoglyphs in pampas and canyons around the down basins of the central coast valleys of Peru. The purpose of the present work is to evaluate the collected information and to give some additional details about three archaeological places in the left margin of the valley of Chillon river. These places don’t exist any more, because the urban development, and they were found thanks to old aerial photos and historical cartographie of the zone. The geoglyphs are described in relation to the archaeological places and routes connecting the down valley of the Chillon river and the Canto Grande Pampa, where one of the biggest rock art centers can be found.